The Role of AI in Energy Usability and Efficiency: Opportunities and Limitations - Szeberényi, András; Rokicki, Tomasz; Bozsik, Norbert (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Artificial Intelligence (AI) is increasingly shaping environmental sustainability, particularly in optimizing energy usability and enhancing energy efficiency. AI-powered solutions, such as smart grids, predictive analytics, and automated energy management systems, enable real-time monitoring and dynamic energy allocation, reducing waste and improving overall efficiency. AI-driven forecasting models also enhance renewable energy integration by predicting fluctuations in solar and wind power generation, ensuring a more stable and sustainable energy supply. Additionally, AI-enabled IoT systems contribute to energy-efficient buildings and industrial processes by autonomously regulating energy consumption based on real-time data. This study employs a mixed-method research approach, combining secondary data analysis with primary research. The primary research component consists of four in-depth interviews with experts in AI, and energy management. These interviews provided qualitative insights into the practical applications, challenges, and future potential of AI-driven energy solutions. The main findings indicate that while AI significantly contributes to energy optimization and stabilization, it also poses sustainability challenges due to its high energy consumption. Experts emphasized that AI-driven solutions must evolve towards greater energy efficiency to offset the environmental impact of AI infrastructure itself.